2016
DOI: 10.1007/s00262-016-1908-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of CD8+ tumor-infiltrating lymphocytes in non-small-cell lung cancer: impact on patient prognostic assessments and comparison of quantification by different sampling strategies

Abstract: Introduction Infiltration of non-small-cell lung cancer (NSCLC) by CD8+ T lymphocytes predicts improved patient survival; however, heterogeneity of intratumoral localization complicates this assessment. Strategies for tumor sampling may not accurately represent the whole tumor. We hypothesized that sampling strategies may alter the identification of tumors with high CD8 density and affect the prognostic significance. Patients and methods Twenty-three primary NSCLC tumors were immunohistochemically stained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…However, a large biopsy of one tumor may be representative of multiple synchronous metastases 40 . Also by modeling different ways to sample a lung cancer, we found that different sampling strategies yield different densities of CD8 + infiltrate, but that the values most concordant with whole tumor counts were predicted by a random core sampling of the tumor or sampling of the tumor center 41 . These studies support our approach of using triplicate or quadruplicate 1 mm diameter cores from each tumor specimen as a reasonable representation of the tumor.…”
Section: Discussionmentioning
confidence: 94%
“…However, a large biopsy of one tumor may be representative of multiple synchronous metastases 40 . Also by modeling different ways to sample a lung cancer, we found that different sampling strategies yield different densities of CD8 + infiltrate, but that the values most concordant with whole tumor counts were predicted by a random core sampling of the tumor or sampling of the tumor center 41 . These studies support our approach of using triplicate or quadruplicate 1 mm diameter cores from each tumor specimen as a reasonable representation of the tumor.…”
Section: Discussionmentioning
confidence: 94%
“…As this is a study of an RNA-seq clinical database, our findings need to be validated at the protein level in future studies. Another shortcoming of this study is that TCGA tumor samples are core biopsies or incisional biopsies, which may not be a reliable representative of the entire tumor 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, variation in immune cell infiltrates within cellular areas is likely to occur throughout the tumour, and the use of tissue archives in this study eliminated our ability to correlate findings with the location of the sample within tumour (ie, center vs invasive margin). Future studies should consider the prospective collection of large portions of tumour from randomly selected sites in order to best represent the tumour as a whole …”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider the prospective collection of large portions of tumour from randomly selected sites in order to best represent the tumour as a whole. 61 An important limitation of this study is the selection for cases undergoing a necropsy at the VMTH. This resulted in an overrepresentation of cOSA cases presenting with metastasis at diagnosis, in addition to those experiencing rapid cancer progression since they are more likely to still have a relationship with our hospital.…”
Section: Discussionmentioning
confidence: 99%